Political communication strategies in Panchayati Raj election: observation study of Kangra District of Himachal Pradesh- India - Fakira Mohan Nahak; Nidhi Sharma (Komunitas Ilmuwan dan Profesional Muslim Indonesia (KIPMI), 2022)
India's Himachal Pradesh region is a home for several villages in which its rural political system named Panchayati Raj (PR) is increasingly influential in the state. Recently, the state holds the elections for the Panchyati Raj. The local people are enthusiastically engaged in the election and exhibited interest in voting in general and youth voting in particular. The results of the Panchyati Raj election portray the picture of all the political parties and their influence in the state. All parties emphasize the need of connecting with people through communication. The state's literacy rate is another intriguing feature in which, the state, despite living in countryside, has the second-highest percentage of literacy after Kerala. As a result, the populace as a whole are more informed and responsive to communication. It was noted that both traditional and contemporary media have been used throughout the election to communicate with the public. The current study examines the communication tactics used by all political parties in the Panchyati Raj election in the Himachal Pradesh’s district of Kangra. It is only 5.71% of the people of Kangra district residing in urban areas; while the remainder reside in rural ones. The culturally appropriate communication methods among villagers become more significant in this election. This study then aims to observe the communication tools, language (mother tongue), development issues and key factors of participants such as resident, life style, or education (villagers and candidates). The researchers used an observation study as a non-participatory means through interview tool and used content analysis method for data analysis. The results of this study showed that Pahari (people living in high terrains) were more connected with their traditional culture including communication pattern, lifestyle along with concerned with roots development.